Antimicrobial peptides β-defensin family: Expression and regulation in the endometrium during the estrous cycle and pregnancy in pigs. (February 2023) - Lee, Soohyung; Yoo, Inkyu; Cheon, Yugyeong; Hong, Minsun; Jeon, Bo-Young; Ka, Hakhyun
Abstract: Members of the β-defensin (DEFB) family, which are antimicrobial peptides and humoral components of the innate immune system, protect the surfaces of various host tissues by killing a broad range of microorganisms and are involved in immunomodulatory actions. The expression of these DEFB members changed during the estrous cycle and pregnancy in a stage-specific manner. The expression of DEFBs was also detected in conceptus and chorioallantoic tissues during pregnancy. DEFB1 and DEFB3 proteins and DEFB2 mRNA were localized primarily to endometrial epithelial cells during early pregnancy. Increasing doses of progesterone upregulated DEFB2 and EP2C expression in endometrial explant tissues. These results showed that members of the DEFB family were expressed stage-specifically at the maternal-conceptus interface in pigs, suggesting that the DEFB family plays important roles at the maternal-conceptus interface in regulation of innate immunity by protection of the maternal endometrial and conceptus tissues from pathogens to preserve fertility in pigs. Highlights: Antimicrobial peptides  DEFBs  are stage-specifically expressed in the endometrium during the estrous cycle and pregnancy. DEFB1 protein is localized primarily to epithelial cells in the endometrium and  DEFB2  mRNA to luminal epithelial cells. DEFBs are expressed in early-stage conceptuses and chorioallantoic tissues from mid-to term pregnancy. The expression of DEFB2 and EP2C is induced by progesterone in endometrial explant tissues. Abstract : Summary: β-defensins are expressed in the porcine endometrium during the estrous cycle and pregnancy.